ANALISIS TINGKAT KEPUASAN ORGANISASI PERANGKAT DAERAH (OPD) DAN REKANAN TERHADAP KINERJA BIRO ADMINISTRASI PENGADAAN BARANG/JASA PEMERINTAH PROVINSI BALI - Parami Dewi, Anak Agung Diah; Anom Wiryasa, Ngakan Made; Atmaja, I Gede Bayu Kurnia (JURNAL SPEKTRAN; Vol 7 No 1 (2019): Vol. 7, No.1, Januari 2019, 2019)
ANALYSIS OF SATISFACTION LEVEL ORGANIZATION LEVEL (OPD) AND PARTNERS TO PERFORMANCE BUREAU ADMINISTRATION PROCUREMENT OF GOVERNMENT SERVICES / PROVINCIAL SERVICES BALI ABSTRACT             The performance accountability of the Procurement Administration Bureau of Bali Province is required in construction project tender process in order to avoid distrust of the partners as auctioneer. The purpose of this research is to analyze the level of satisfaction of Regional Work Agency and partner to the performance of the Procurement Administration Bureau and dominant factors that influence Regional Work Agency’s satisfaction and partners to Procurement Administration Bureau of Bali Province. The research was conducted at the Procurement Administration Bureau of Bali Province. Data collection was conducted using questionnaire survey.  Questionnaires were administered to 51 respondents.   Subsequently, data was analyzed using regression analysis.  Data analysis shows that  there is a significant influence of the satisfaction level of Regional Work Agency (OPD) to the performance of Procurement Administration Bureau of Bali Province with the level of significance a <0.05. There is also a significant influence of the satisfaction level of partners to the performance of Procurement Administration Bureau of Bali Province with the level of significance a <0.05. The most dominant factors affecting the partnership satisfaction are the dimensions of reliability with the value of Standardized Coefficients Beta of 23.8%, followed by empathy of 22.4%, tangible of 21.7%, responsiveness of 19.6% and assurance of 15.9 %. The most dominant factor affecting the satisfaction of Organization of Regional Device (OPD) is assurance dimension with Standardized Coefficients Beta value of 29.2%, followed by empathy of 25.1%, reliability of 20.5%, tangible of 17.6% and responsiveness of 15.8%.